An empirical study on ‘how to retain rural teachers with emphasis on hygiene or motivation factors’: A case of Western China - Jiang, Jin-Qiu; Yao, Jie; Yu, Kai-Rui; Li, Chong-Nan (Frontiers in Psychology, 2023)
How to retain prominent teachers is a fundamental problem for rural education in less developed countries. However, the critical institutional factors affecting teachers’ turnover intention still need to be better understood. According to Herzberg’s motivation-hygiene theory, this study examines the effects of hygiene factors (rural incentive policy, personnel policy, and teacher pay) and motivation factors (advancement, work itself, and achievement) on rural teachers’ turnover intention. Based on a sample of 973 rural teachers, the results from structural equation modeling (SEM) showed that both hygiene factors and motivation factors can significantly reduce the turnover intention of rural teachers. Meanwhile, the effect of motivation factors is greater than that of hygiene factors. It was also confirmed that marital status, age, and teaching subject have a significant moderation effect on the relationship between motivation/hygiene factor and turnover intention, whereas gender has no significant moderation effect. Theoretical and practical implications for attracting and retaining rural teachers are discussed.